Contrasting changes in taxonomic, phylogenetic and functional diversity during a long‐term succession: insights into assembly processes. (31st May 2013) - Purschke, Oliver; Schmid, Barbara C.; Sykes, Martin T.; Poschlod, Peter; Michalski, Stefan G.; Durka, Walter; Kühn, Ingolf; Winter, Marten; Prentice, Honor C.; Fridley, Jason
Summary Theory predicts that the processes generating biodiversity after disturbance will change during succession. Comparisons of phylogenetic and functional (alpha and beta) diversity with taxonomic diversity can provide insights into the extent to which community assembly is driven by deterministic or stochastic processes, but comparative approaches have yet to be applied to successional systems. We characterized taxonomic, phylogenetic and functional plant (alpha and beta) diversity within and between four successional stages in a > 270‐year‐long arable‐to‐grassland chronosequence. Null models were used to test whether functional and phylogenetic turnover differed from random expectations, given the levels of species diversity. The three facets of diversity showed different patterns of change during succession. Between early and early‐mid succession, species richness increased but there was no increase in functional or phylogenetic diversity. Higher than predicted levels of functional similarity between species within the early and early‐mid successional stages, indicate that abiotic filters have selected for sets of functionally similar species within sites. Between late‐mid and late succession, there was no further increase in species richness, but a significant increase in functional alpha diversity, suggesting that functionally redundant species were replaced by functionally more dissimilar species. Functional turnover between stages was higher than predicted, and higher than within‐stage turnover, indicating that different assembly processes act at different successional stages. Synthesis. Analysis of spatial and temporal turnover in different facets of diversity suggests that deterministic processes generate biodiversity during post‐disturbance ecosystem development and that the relative importance of assembly processes has changed over time. Trait‐mediated abiotic filtering appears to play an important role in community assembly during the early and early‐mid stages of arable‐to‐grassland succession, whereas the relative importance of competitive exclusion appears to have increased towards the later successional stages. Phylogenetic diversity provided a poor reflection of functional diversity and did not contribute to inferences about underlying assembly processes. Functionally deterministic assembly suggests that it may be possible to predict future post‐disturbance changes in biodiversity, and associated ecosystem attributes, on the basis of species' functional traits but not phylogeny.